Bacterial Extracellular Vesicles and the Gut‐Microbiota Brain Axis: Emerging Roles in Communication and Potential as Therapeutics. Issue 7 (15th April 2021) - Pirolli, Nicholas H.; Bentley, William E.; Jay, Steven M.
Abstract: Bacterial extracellular vesicles (BEVs) have emerged as candidate signaling vectors for long‐distance interkingdom communication within the gut‐microbiota brain axis. Most bacteria release these nanosized vesicles, capable of signaling to the brain via their abundant protein and small RNA cargo, possibly directly via crossing the blood‐brain barrier. BEVs have been shown to regulate brain gene expression and induce pathology at most stages of neuroinflammation and neurodegeneration, and thus they may play a causal role in diseases such as Alzheimer's, Parkinson's, and depression/anxiety. On the other hand, BEVs have intrinsic therapeutic properties that may be relevant to probiotic therapy and can also be engineered to function as drug delivery vehicles and vaccines. Thus, BEVs may be both a cause of and solution to neuropathological conditions. In this review, current knowledge of the physiological roles of BEVs as well as state of the art pertaining to the development of therapeutic BEVs in the context of the microbiome‐gut‐brain axis are summarized. Abstract : Bacteria in the gut microbiome release bacterial extracellular vesicles (BEVs) that can induce neurologic effects indirectly via increasing systemic inflammation and increasing blood‐brain barrier (BBB) permeability, and directly via crossing the BBB and activating microglia and altering gene expression. The ability of BEVs to modulate the nervous system endows therapeutic potential for neurologic diseases via the employment of probiotics and/or synthetic biology and bioengineering.